2018
DOI: 10.1038/s41419-018-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

The pro-inflammatory phenotype of the human non-classical monocyte subset is attributed to senescence

Abstract: Human primary monocytes comprise a heterogeneous population that can be classified into three subsets based on CD14 and CD16 expression: classical (CD14high/CD16−), intermediate (CD14high/CD16+), and non-classical (CD14low/CD16+). The non-classical monocytes are the most pro-inflammatory in response to TLR stimulation in vitro, yet they express a remarkably high basal level of miR-146a, a microRNA known to negatively regulate the TLR pathway. This concurrence of a pro-inflammatory status and a high miR-146a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
151
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(180 citation statements)
references
References 58 publications
14
151
1
3
Order By: Relevance
“…The vaccine not only maintained a large number of tumor antigens, but also maintained high local cytokine concentrations. 27 In the present study, we induced 4T1 cells into senescent status and found higher concentrations of immunostimulatory cytokines, including IFN-c, TNF-a, IL-17 and IL-12P70. Meanwhile, we assessed secretion of TGF-b, IL-12P40 and IL-10.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The vaccine not only maintained a large number of tumor antigens, but also maintained high local cytokine concentrations. 27 In the present study, we induced 4T1 cells into senescent status and found higher concentrations of immunostimulatory cytokines, including IFN-c, TNF-a, IL-17 and IL-12P70. Meanwhile, we assessed secretion of TGF-b, IL-12P40 and IL-10.…”
Section: Discussionsupporting
confidence: 54%
“…E, Survival curves of mice in different groups remains viable and metabolically active. 27 Our study showed that an accumulation of senescent cells with various SASP would cause proinflammatory microenvironments. This suggested the possibility to exploit a novel vaccine different from conventional vaccines.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…monocytes, dendritic cells and NK cells) are not annotated by any of their known subtypes. Nevertheless, PARC is able to reveal the clusters showing high expression of CD14 (cluster 9) and CD16 (or FCGR3A) (cluster 10), markers for classical and non-classical monocytes respectively (Ong, 2018). It also identifies subsets of NK cells as inferred by the expression level of CD160 and CD16 (FCGR3A) (cluster 3 and 5), which is known to be associated to the CD56dim CD16+ cytotoxic NK cell phenotype (cluster 5) (Bouteiller, 2011).…”
Section: Pbmcs and 13 Million Mouse Brain Cellsmentioning
confidence: 99%